Traffic Counting using YOLO Version-8 (Case Study of Jakarta-Cikampek Toll Road) - Darmadi, Darmadi; Pratikso, Pratikso; Rahmat, Mudiyono (ASTONJADRO, 2024)
You Only Look Once (YOLO) version 8 is the latest version of YOLO. YOLO is a common object detection model that offers faster and more accurate results. YOLO applications provide numerous benefits in the fields of health care, traffic control, vehicle safety, energy, agriculture, and industry. The purpose of this article is to use advancements in information technology to automate the process of manually recording traffic counts on the highway. The method utilized in this study is to record a video of traffic movements with a smartphone camera and save it in MP4 format. Calculations are performed at the office after receiving recorded video and utilizing a program written by the author that makes use of Python, Ppencv, Pytorch, and YOLO version 8 software. When passing through a counter box, the traffic volume is counted and saved in Excel format (.xls). The video records footage near the Halim area of the Jakarta-Cikampek toll road. With a measurement accuracy of 99.63% for cars, 96.66% for buses, and 98.55% for trucks, the accuracy attained using YOLO version 8 is fairly satisfactory for detecting vehicle volume and categorization.